Numerical study on plastic hinge formation on steel beams : stress strain, deflection and rotation angle profiles - Goh, Choon Siong. (2012)
In this numerical study, three dimensional analyses were carried out using finite element method to evaluate the plastic behavior of RHS cold-formed steel beams, particularly focus on the plastic hinge formation. Commercial software, ABAQUS/CAE is used for modelling. Cold-formed Rectangular Hollow Section (RHS) of geometry 75mm x 50mm x 6mm is selected for the test specimens. Two types of test are conducted, with one type is of 75mm x 50mm x 6mm configuration and another one of 50mm x 75mm x 6mm configuration. The experimental setup is propped cantilever with one end being fixed support by welding and the other end being rested on roller support. A concentrated transverse load is applied on the mid span of specimens until two plastic hinges are formed.